Periodontitis in Rats Induces Systemic Oxidative Stress That Is Controlled by Bone-Targeted Antiresorptives - (:unkn) unknown (WILEY, 2015)
Background: Periodontitis is a chronic, polymicrobial inflammatory disease that degrades connective tissue and alveolar bone and results in tooth loss. Oxidative stress has been linked to the onset of periodontal tissue breakdown and systemic inflammation, and the success of antiresorptive treatments will rely on how effectively they can ameliorate periodontal disease-induced oxidative stress during oral infection. Methods: Rats were infected with polybacterial inoculum consisting of Porphyromonas gingivalis, Treponema denticola, and Tannerella forsythia, as an oral lavage every other week for 12 weeks. Daily subcutaneous injections of enoxacin, bis-enoxacin, alendronate, or doxycycline were administered for 6 weeks after 6 weeks of polybacterial infection in rats. The serum levels of oxidative stress parameters and antioxidant enzymes, including glutathione peroxidase, superoxide dismutase, and catalase, were evaluated in each of the infected, treated, and sham-infected rats. Results: Rats infected with the periodontal pathogens displayed a five-fold increase in the oxidative stress index compared with controls as a result of increased levels of serum oxidants and decreases in total antioxidant activity. The overall decrease in antioxidant activity occurred despite increases in three important antioxidant enzymes, suggesting an imbalance between antioxidant macromolecules/small molecules production and antioxidant enzyme levels. Surprisingly, the bone-targeted antiresorptives bis-enoxacin and alendronate inhibited increases in oxidative stress caused by periodontitis. Bis-enoxacin, which has both antiresorptive and antibiotic activities, was more effective than alendronate, which acts only as an antiresorptive. Conclusion: To the best of the authors' knowledge, this is the first study to demonstrate that the increased oxidative stress induced by periodontal infection in rats can be ameliorated by bone-targeted antiresorptives.
Keywords: Alendronate; bacteria; periodontal; enoxacin; lipid peroxidation; oxidative stress; periodontal diseases; VACUOLAR H+-ATPASE; GINGIVAL CREVICULAR FLUID; LIPID-PEROXIDATION LEVELS; TOTAL OXIDANT STATUS; DNA-DAMAGE; ANTIOXIDANT; DISEASE; ENOXACIN; RESORPTION; OSTEOCLASTOGENESIS